ANALISIS PENOLAKAN PERMOHONAN PERNYATAAN PAILIT TERHADAP PT AKU DIGITAL INDONESIA (AKUMOBIL) (STUDI KASUS: PUTUSAN MA NOMOR 831 K/PDT.SUS-PAILIT/2020) - Aksses Patrick Boike Pane; Ariawan Ariawan (Jurnal Hukum Adigama, 2021)
This writing aims to find out whether the Judge's Consideration on Decision No. 831 K / Pdt.SusBankruptcy / 2020 which strengthens theJudge's Decision No. 56 K / Pdt.Sus-Bankruptcy / 2019 / PN. Niaga.Jkt.Pst to reject the bankruptcy statement application against PT Aku Digital Indonesia (Akumobil) has been in accordance with the Law. In this case, the Judge's consideration at the first level and cassation are slightly wrong because the judge states that there is a debt that is not due and there is a criminal element that makes the proof not simple. Whereas in article 2 paragraph 1 of Law No. 37 of 2004 concerning Insolvency and Delay of Debt Payment Obligations mentions that bankruptcy applications can be filed by Debtors who have two or more Creditors and do not pay off at least one debt that has matured and can be billed, which in fact based on the statement in the Vehicle Booking Letter owned by consumers there is debt that is due. The existence of criminal elements does not make the case unassuming because article 8 paragraph 4 of Law No. 37 of 2004 concerning Bankruptcy and Delay of Debt Payment Obligations stipulates that simple proof can be declared insolvent referring to Article 2 paragraph 1 so that the bankruptcy application against PT Aku Digital Indonesia (Akumobil) can be granted by the Judge. Therefore, the Judge must uphold legal certainty in accordance with Law No. 37 of 2004 concerning Insolvency and Delay of Debt Payment Obligations